Early recognition of familiar word-forms as a function of production skills - Lorenzini, Irene; Nazzi, Thierry (Frontiers in Psychology, 2022)
Growing evidence shows that early speech processing relies on information extracted from speech production. In particular, production skills are linked to word-form processing, as more advanced producers prefer listening to pseudowords containing consonants they do not yet produce. However, it is unclear whether production affects word-form encoding (the translation of perceived phonological information into a memory trace) and/or recognition (the automatic retrieval of a stored item). Distinguishing recognition from encoding makes it possible to explore whether sensorimotor information is stored in long-term phonological representations (and thus, retrieved during recognition) or is processed when encoding a new item, but not necessarily when retrieving a stored item. In this study, we asked whether speech-related sensorimotor information is retained in long-term representations of word-forms. To this aim, we tested the effect of production on the recognition of ecologically learned, real familiar word-forms. Testing these items allowed to assess the effect of sensorimotor information in a context in which encoding did not happen during testing itself. Two groups of French-learning monolinguals (11- and 14-month-olds) participated in the study. Using the Headturn Preference Procedure, each group heard two lists, each containing 10 familiar word-forms composed of either early-learned consonants (commonly produced by French-learners at these ages) or late-learned consonants (more rarely produced at these ages). We hypothesized differences in listening preferences as a function of word-list and/or production skills. At both 11 and 14 months, babbling skills modulated orientation times to the word-lists containing late-learned consonants. This specific effect establishes that speech production impacts familiar word-form recognition by 11 months, suggesting that sensorimotor information is retained in long-term word-form representations and accessed during word-form processing.